Courtney Fichter: capstone - Fichter, Courtney, artist (Colorado State University. Libraries, 2022)
The artist's statement: My body of work is focused on conceptual experimental video. I very much focus on centering my themes in each video around my own lived experiences. These topics have expanded from anxiety, mental health, and cultural differences within locations. I utilize sound and samples to bring the viewer discomfort when watching my work. I often utilize looping to create a monotonous yet uncomfortable experience. Sound is an integral part of the viewing experience of my work as it turns mundane, average shots to something else.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art